Reducing alcohol consumption during pre-drinking sessions: testing an integrated behaviour-change model - Caudwell, K.; Keech, J.; Hamilton, K.; Mullan, B.; Hagger, Martin (Routledge, 2019)
Objective: Pre-drinking, the practice of consuming alcohol prior to attending a subsequent event, increases the risk of alcohol-related harm, and is common in undergraduate student populations. The current study tested an integrated behaviour change model to identify the motivational, social-cognitive, and implicit predictors of pre-drinking. Design: University students (N = 289) completed an online questionnaire comprising measures of motivational and social-cognitive constructs related to reducing pre-drinking alcohol consumption and past behaviour, and an implicit association test for drinking identity. Participants reported their pre-drinking alcohol consumption at follow-up, 4 weeks from baseline. Main Outcome Measures: Self-reported pre-drinking alcohol consumption. Results: A variance-based structural equation model revealed that few model hypotheses were supported. Although the effects of past behaviour, perceived behavioural control, and implicit drinking identity, on follow-up pre-drinking alcohol consumption were statistically significant, the effect of intention was not. Conclusions: Current findings indicate pre-drinking alcohol consumption is associated with past behaviour, perceived behavioural control and implicit drinking identity, and no intentions to reduce pre-drinking alcohol consumption. The finding raise questions over the validity of applying the integrated model in this context. Interventions should consider these factors and attempt to facilitate the formation of intentions that lead to subsequent behaviour.